Pemikiran Ibnu Khaldun dalam Strategi Pelaksanaan Iklim Dini Di Sekolah: Ibn Khaldun's Thoughts on Early Climate Implementation Strategies in Schools - Arifin, Raihan Bin Mohd; Mat Teh, Kamarul Shukri bin; Amrullah, Muhlasin (Pedagogia : Jurnal Pendidikan, 2018)
Ibn Khaldun is one of the leaders and Islamic thinkers of sociology, education, politics and economics. The scholars acknowledge their masterpiece al-Mukadimah as a source of study and references to this day. The purpose of this study is to examine strategies according to Ibn Khaldun's thinking in implementing Islamic school climate in order to be used as a guide and adapted in school. This qualitative study uses content analysis. This study finds that the Islamic school climate-implementation strategy proposed by Ibn Khaldun is very useful for adoption and practice by today's educators. This paper takes Ibn Khaldun's views from various scopes including environmental theory, strategy and thought. As a result of this study, a framework related to Islamic school climate implementation strategies has also been proposed